PERSEPSI TERHADAP DUKUNGAN ORGANISASI DAN PENYELIA, KEPUASAN, NILAI, DAN KOMITMEN PADA INDUSTRI PERBANKAN INDONESIA - D. Wahyu Ariani (University of Merdeka Malang, 2011)
Perceived support and values similarity had an effect on organizational behavior outputs such as organizationalcommitment and job satisfaction. Perceived support comprised perceived organizational support andperceived supervisor support. Perceived supervisor support influenced perceived organizational support.This study examined the relationship between perceived organizational supports (POS), perceived supervisorsupport (PSS), values similarities, job satisfaction, and affective organizational commitment. This study usedsocial exchange theory, psychological contract theory, organizational support theory, social identity theory,and norm of reciprocity to develop the model. We used Structural Equation Modeling (SEM) sample consistingof 392 individuals from banking industry. Consistent with prior literature, our hypothesized modelconfirmed that values similarity was a predictor of PSS and POS, and PSS was a predictor of POS. Thefindings indicated that as employees perception of organizational support increase, their affective organizationalcommitment and job satisfaction significantly increase.